Cyborg networks: freedom through data with open source and implantable devices (Annals of the University of Bucharest. Philosophy Series, 2025)
Implantable computing technologies are the blueprint for the ongoing process of cyborgization. Already with the present devices, design decisions and computational issues blend together with a living organism, so that our health, for example, depends on well-adjusted information security, which requires constant work and decisions by many actors of different expertise. This means that implantable technologies form important sociotechnical systems. I will explore cyborg vulnerabilities found in sociotechnical systems, but take seriously the proposed development model of open-source technologies, promising existing and future cyborgs more autonomy and freedom. However, I want to take this vision further. Given the number of technologies that matter in the context of cyborgs, it becomes necessary to look at a wider application of open source, needing more experts and quicker data exchange. While offering a technological solution to make the data exchange possible, granting the users freedoms and autonomy, I also find it important to address how the debates around open source move from software to a large-scale social consideration, should the solution be implemented.
Keywords: cyborg; open source; sociotechnical systems; implantable technologies; data exchange